Analysis of the Budgetary Classification in the Health Subsystem of the Colombian Military Forces, for the fiscal term 2021 (2020)
The Budget Account Classifier regulated by Regulatory Decrees Nos. 1068 of 2015 and 412 of 2018, have been a fundamental basis for the Ministry of Finance and Public Credit, to issue guidelines by which entities that are part of the General Budget of the Nation, implement and apply in a standardized manner, the classification of expenditure through a code , which makes the type and nature of the expenditure identifiable in order to make the management of the entities measurable in terms of the budgetary execution of the resources allocated to them.